PENGARUH RASIO LIKUIDITAS DAN RASIO AKTIVITAS TERHADAP PROFITABILITAS PADA SEKTOR PERTANIAN TBK PERIODE 2019-2020 - Nadia Ayu Malinda; Dwi Lesno Panglipursari (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to examine and analyze the effect of handity ratio and activity ratio on profitability in the agricultural sector listed on the Indonesia Stock Exchange, partially or simultaneously. This type of associative research is causal with a quantitative approach. There are 26 companies listed in the Indonesian Stock Exchange on the Indonesian Stock Exchange, and with purposive sampling technique, 24 companies are obtained as research samples. The data analysis technique uses multiple linear analysis techniques using SPSS version 26. Based on the results of data analysis using the test it is known that partially the liquidity ratio and activity ratio have no significant effect on profitability, while based on the F test it is known that the liquidity ratio and activity ratio are simultaneously no significant effect on profitability.